Drinking careers : a twenty-five-year study of three Navajo populations - Kunitz, Stephen J. (Yale University Press, 1994)
In this book, the first long-term follow-up study of alcohol use among Native Americans, a physician and sociologist and an anthropologist examine the data on three groups of Navajos whom they first interviewed about their use of alcohol in 1966. The authors find verification for their initial hypothesis that young men who would have been classed as alcoholic often stop or moderate their drinking as they age. They also find that there is considerable diversity in the patterns of alcohol use among both women and men.